2013
DOI: 10.1186/1757-1146-6-5
|View full text |Cite
|
Sign up to set email alerts
|

A review of the foot function index and the foot function index – revised

Abstract: BackgroundThe Foot Function Index (FFI) is a self-report, foot-specific instrument measuring pain and disability and has been widely used to measure foot health for over twenty years. A revised FFI (FFI-R) was developed in response to criticism of the FFI. The purpose of this review was to assess the uses of FFI and FFI-R as were reported in medical and surgical literature and address the suggestions found in the literature to improve the metrics of FFI-R.MethodsA systematic literature search of PubMed/Medline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 96 publications
1
134
0
7
Order By: Relevance
“…The revised Foot Function Index, a valid and reliable self-report measure of foot function, was used to describe functional status. 2 The arch height index (AHI) was calculated for all participants to determine foot posture. Briefly, the AHI was calculated by dividing the height of the dorsum of the foot by the truncated foot length (defined as the length from first metatarsal joint line to the back of the heel).…”
Section: T T Conclusionmentioning
confidence: 99%
“…The revised Foot Function Index, a valid and reliable self-report measure of foot function, was used to describe functional status. 2 The arch height index (AHI) was calculated for all participants to determine foot posture. Briefly, the AHI was calculated by dividing the height of the dorsum of the foot by the truncated foot length (defined as the length from first metatarsal joint line to the back of the heel).…”
Section: T T Conclusionmentioning
confidence: 99%
“…Pain is used as a primary outcome measure in many such studies because it is the reason most patients seek treatment and for which practitioners prescribe orthoses [20]. The Foot Function Index (FFI) is indicated for the assessment of treatment outcomes in rheumatology [21] and has been used in a number of trials involving the assessment of orthoses in rheumatoid feet. SooHoo et al [22] performed a study which demonstrated increased responsiveness of foot and ankle specific outcomes tools compared to the SF-36.…”
Section: Page 6 Of 24mentioning
confidence: 99%
“…Foot Function Index Pain Subscale (FFI) for functional disability: 30,31 The FFI was used to obtain information on the impact of the patients' foot pain on their daily activities. It was found to be a valid and reliable scale for measuring foot pain, disability and activity restriction in orthopedic interventional trials and in patients with plantar fascitis.…”
Section: Numerical Pain Rating Scale-101(nprs-101)mentioning
confidence: 99%